Composite cardiovascular risk factor target achievement and its predictors in US adults with diabetes: The Diabetes Collaborative Registry. Issue 5 (14th February 2019) - Fan, Wenjun; Song, Yang; Inzucchi, Silvio E.; Sperling, Laurence; Cannon, Christopher P.; Arnold, Suzanne V.; Kosiborod, Mikhail; Wong, Nathan D.
Abstract : Aim: To investigate multiple risk factor target attainment in adults with diabetes mellitus (DM) for atherosclerotic cardiovascular disease (ASCVD) prevention and the predictors of such attainment in a contemporary DM registry. Methods: In the US Diabetes Collaborative Registry we identified patients who were at target for glycated haemoglobin (HbA1c; < 53 mmol/mol (7%) or < 64 mmol/mol (8%) if with ASCVD), LDL cholesterol (< 2.6 mmol/L (100 mg/dL) or < 1.8 mmol/L (70 mg/dL) 1.8 if with ASCVD) and blood pressure (BP; <140/90 mmHg and < 130/80 mmHg as an alternate), and who had non‐smoking status, by sex, race and history of ASCVD. Multiple logistic regression was used to examine predictors of target attainment. Results: In 74 393 patients with DM who had available data (mean age 69.0 years, 41.0% women), overall target attainment for HbA1c, BP, LDL cholesterol and non‐smoking status was 73.6%, 69.0% (40.3% for BP <130/80 mmHg), 48.6% and 85.2%, respectively. Only 21.6% (13.0% with BP <130/80 mmHg) were at target for all four measures, and the proportions were higher in men (23.6%) versus women (18.6%) and in white people (22.5%) versus African‐American people (14.7%) and people of other races (20.8%; P < 0.01). A total of 62.4% were on a moderate‐/high‐intensity statin. Age (≥65 years: odds ratio [OR] 1.9, 95% confidence interval [CI] 1.7‐2.0; and 55‐64 years: OR 1.3, 95% CI 1.2‐1.4 vs. <55 years), male sex (OR 1.3, 95% CI 1.3‐1.4), white race (OR 1.4, 95% CI 1.3‐1.5), middle or high income (ORs 1.1, 95% CI 1.1‐1.2 or 1.4, 95% CI 1.4‐1.5, respectively) were associated, and depression (OR 0.9, 95% CI 0.8‐1.0) was inversely associated with meeting all four targets (all P = 0.01 to P < 0.001). Conclusions: In our US registry of patients with DM, only one in five patients were achieving comprehensive risk factor control. Multifactorial interventions will be necessary to optimize ASCVD risk factor control.